Pengembangan Game Edukasi IPA “Rantai Makanan dan Ekosistem” Berbasis Kuis Interaktif Kahoot untuk Siswa Kelas V - Diva Amilia Ramadhani; Ika Putra Viratama (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Strengthening scientific literacy in elementary science learning requires interactive and contextual instructional strategies. Game-based learning has been shown to enhance student motivation and engagement (Clark et al., 2016). This study aims to develop and examine the effectiveness of an interactive quiz-based educational game on the topic of food chains and ecosystems for fifth-grade students. The research employed a Research and Development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages (Yusuf & Rahman, 2023). The participants were 25 students. Data were collected through pretest and posttest instruments and analyzed using the N-Gain formula to measure learning improvement. The findings indicate a moderate to high increase in students’ learning outcomes after the implementation of the developed media. In addition, students demonstrated greater participation during the learning process. These results suggest that interactive quiz-based educational games can serve as an effective alternative strategy to enhance conceptual understanding in elementary science education.